Contribution of Genotype, Environment and Management Components on Rice Yield and Strategy for Yield Enhancement in Fallow - Parvin, N; Salam, M A; Salam, M U; Kader, M A; Mamun, M A A; Nessa, B; Hasan, A K (Bangladesh Agronomy Journal, 2025)
Genotype (G), environment (E) and management (M) form a triangular association in realizing grain yield of T. Aman rice. G expresses its yield potential when grown in right E under appropriate M. This study presents additive contribution of these three GEM components to grain yield of the crop. This study was undertaken to develop a GEM-based framework and use it in prioritizing strategic avenues for enhancement of rice in the Fallow-T. Aman-Fallow cropping system. Partitioning of grain yield of rice into G, E and M components was done following standard principle using 4491 research data-points from one decade’s experiments (2010 to 2019) conducted by the Bangladesh Rice Research Institute. Results showed under the high yield potential varieties, G differences justified 29.5%, E 48.9% and M 21.6% variation in grain yield. The relative contribution of GEM components was not static across the years. As time advanced (from 2010), the contribution of G in explaining grain yield was found gradually reducing, whereas the contribution of E and M increasing. In the interrelationship between the three GEM components, the contribution of G was almost static and M was negative across E. The yield response specific to G, considering the two prominent rice varieties, BR11 and BRRI dhan49 was very narrow (4.60 to 4.68 t ha−1), whereas E and M was much wider (3.53 t ha−1 respectively). Two varieties did not equally respond to all management. Furthermore, the grain yield from the same management responded differently to E (both location and year). While E and M are the triggering points for yield improvements in T. Aman rice, minimizing yield gap among the E by physical interventions is not a likely option. This study provides three pathways of linking M to yield improvements in T. Aman rice management in relation to genotype, location and growing season. Hence, it is concluded that for augmenting grain yield of T. Aman rice in the present circumstances, prioritizing M specific to G and E is the practical pathway. Bangladesh Agron. J. 2024, 27(2): 96-107